Humoral and cellular immune response from first to fourth SARS-CoV-2 mRNA vaccination in anti-CD20-treated multiple sclerosis patients—a longitudinal cohort study - Novak, Frederik; Nilsson, Anna Christine; Christensen, Emil Birch; Stougaard, Caroline Louise; Barnkob, Mike Bogetofte; Holm, Dorte K.; Witt, Agnes Hauschultz; Byg, Keld-Erik; Johansen, Isik S.; Nielsen, Christian; Sejbaek, Tobias (Frontiers in Immunology, 2024)
Background This study examines the humoral and cellular response in multiple sclerosis (MS) patients on anti-CD20 therapy before and after the 1st to 4th BNT162b2 mRNA SARS-CoV-2 vaccination and the relationship with breakthrough infection. Methods Participants with McDonald 2017 MS that were treated with ocrelizumab were included. The study duration was throughout the COVID-19 pandemic until four months after fourth mRNA SARS-CoV-2 vaccination (BNT162b2). Longitudinal blood samples were analysed for: IgG antibodies of SARS-CoV-2 spike anti-receptor binding domain (anti-RBD), nucleocapsid IgG antibodies (anti-N) and activation induced marker expressing CD4+, CD8+ T-cells and concentration of ocrelizumab and anti-drug antibodies. Incidences of breakthrough infection were confirmed with SARS-CoV-2 PCR tests. Results The rate of anti-RBD positive participants increased substantially between the third and fourth vaccination from 22.2% to 55.9% (median 54.7 BAU/mL; IQR: 14.5 – 221.2 BAU/mL and 607.7 BAU/mL; IQR: 29.4 – 784.6 BAU/mL, respectively). Within the same period 75% of participants experienced breakthrough infection. The fourth vaccination resulted in an additional increase in seropositive individuals (64.3%) (median 541.8 BAU/mL (IQR: 19.1-1007 BAU/mL). Breakthrough infection did not influence the cellular response without a significant change after the fourth vaccination. During the study period two participants had detectable anti-N, both after the fourth vaccination. No correlation was found between serum concentration of ocrelizumab and the humoral and cellular response. Discussion Low levels or absence of specific anti-RBD following vaccination, with a significant increase after breakthrough infections and boosted by the fourth vaccination. T-cell reactivity remained sustained and unaffected by breakthrough infections.